Obstetric and Neonatal Outcomes in Pregnant Women with Methamphetamine Use Delivering at Nakhon Thai Crown Prince Hospital - Vanitchayakosol, Chariwan (Journal of Health Sciences Sukhothai hospital, 2026)
Background: Methamphetamine use during pregnancy adversely affects both mothers and infants; however, data in the context of community hospitals remain limited. Objective: To compare obstetric and neonatal outcomes between pregnant women who used and did not use methamphetamine at Somdet Phra Yupparat Nakhon Thai Hospital. Methods: A retrospective comparative study was conducted using medical records from October 1, 2017, to September 30, 2025. A total of 207 pregnant women were included, comprising 48 women with methamphetamine detected in urine and 159 women without methamphetamine detected in urine. Data were analyzed using descriptive statistics, Chi-square test, Fisher’s exact test, independent samples t-test, Mann-Whitney U test, and multiple logistic regression. Results: The proportion of inadequate antenatal care was higher among women with methamphetamine detected in urine than among those without methamphetamine detected in urine (66.7% vs. 25.1%; p < .001). The rates of preterm birth (31.3% vs. 10.0%; p = .001), preeclampsia (12.5% vs. 3.1%; p = .021), and low birth weight (33.3% vs. 9.4%; p < .001) were also higher. In addition, fetal death was found only among women with methamphetamine detected in urine (6.3% vs. 0.0%; p = .012). Infants in the methamphetamine-detected group had lower mean body length and mean body temperature at birth, a higher proportion of Apgar scores <7 at 5 minutes, and longer hospital stays. Multiple logistic regression analysis showed that methamphetamine detected in urine was independently associated with low birth weight (aOR = 3.35; 95% CI: 1.67–6.72) and preterm birth (aOR = 3.12; 95% CI: 1.55–6.27). Conclusion: Methamphetamine detected during pregnancy was associated with adverse maternal and neonatal outcomes. These findings support the importance of proactive screening, continuous antenatal care, and multidisciplinary care to reduce complications.